Analisis Insight Instagram Business untuk Pengambilan Keputusan Bisnis yang Lebih Cerdas - Andita, Mirza Putri; Lusiana Annisa, Mutiara; Trinoviyanti, Trinoviyanti; Pramono, Setia (Universitas Multi Data Palembang, 2024)
The utilization of social media, particularly Instagram Business, has emerged as an integral strategy in supporting the sustainability of a business, especially SME. The information provided by Insight Instagram Business, such as statistics of reached audience and profile of audience visiting business Instagram accounts, can be a valuable tool for business owners to optimize marketing or other business strategies. This research aims to evaluate the impact of using Insight on Instagram Business as a tool that supports the business decision making process on the growth of business performance. The research method used in this research is distributing questionnaires to 100 MSME business owners or Instagram admins, who actively use the Insight feature on Instagram. The findings indicate that both comprehension and utilization of data from Insight in Instagram Business independently have a positive impact on business performance.